2021
DOI: 10.3390/cancers13092036
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modulation of Bacteriophages as an Additional Player in Inflammation and Cancer

Abstract: Natural compounds such as essential oils and tea have been used successfully in naturopathy and folk medicine for hundreds of years. Current research is unveiling the molecular role of their antibacterial, anti-inflammatory, and anticancer properties. Nevertheless, the effect of these compounds on bacteriophages is still poorly understood. The application of bacteriophages against bacteria has gained a particular interest in recent years due to, e.g., the constant rise of antimicrobial resistance to antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 162 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…Spot-inoculation of Salmonella was subsequently followed by the application of SalmoFresh after 3 h and the phage cocktail was able to decrease Salmonella populations on lettuce and mung bean sprouts ( Zhang et al, 2019 ). Moreover, green tea extract is a common neutralizer used for phage neutralization, mostly due to its high catechin content ( Dhowlaghar and Denes, 2023 ; Marongiu et al, 2021 ). Nevertheless, sprouts are rich in catechin, too so they serve as a natural neutralizer for phages ( Francis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spot-inoculation of Salmonella was subsequently followed by the application of SalmoFresh after 3 h and the phage cocktail was able to decrease Salmonella populations on lettuce and mung bean sprouts ( Zhang et al, 2019 ). Moreover, green tea extract is a common neutralizer used for phage neutralization, mostly due to its high catechin content ( Dhowlaghar and Denes, 2023 ; Marongiu et al, 2021 ). Nevertheless, sprouts are rich in catechin, too so they serve as a natural neutralizer for phages ( Francis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that orally delivered phages were safer and more effective than intraperitoneally administered phages in inhibiting tumorigenesis in pre-clinical models ( Dabrowska et al, 2005 ). Furthermore, the intake of dietary compounds such as polyphenols, teas, and sweeteners can have the potential to impact the physiology of phages by either inhibiting phage activity or promoting phage responses ( Marongiu et al, 2021 ). Thus, diet is an essential element in the involvement of phages in the combat against GI diseases and cancer progression ( Marongiu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intake of dietary compounds such as polyphenols, teas, and sweeteners can have the potential to impact the physiology of phages by either inhibiting phage activity or promoting phage responses ( Marongiu et al, 2021 ). Thus, diet is an essential element in the involvement of phages in the combat against GI diseases and cancer progression ( Marongiu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the gut phage community maintains dynamic equilibrium under normal physiological conditions, whereas this balance can be disturbed by various factors, such as diet, lifestyle modification or pathological status ( Minot et al., 2011 ; Coughlan et al., 2021 ; Marongiu et al., 2021 ). Advancing evidence has demonstrated that dysbiosis of gut phages may stimulate the development or aggravate the course of diseases, such as periodontal disease, Parkinson’s disease, type 2 diabetes, cancer or gastrointestinal disease ( Azeredo et al., 2016 ; Manrique et al., 2017 ; Ma et al., 2018 ; Tetz et al., 2018 ; Santiago-Rodriguez and Hollister, 2019 ; Maronek et al., 2020 ).…”
Section: Roles Of Gut Phages In Ibd Pathogenesismentioning
confidence: 99%